Moldboard Plowing in Wheat–Fallow Systems of the Pacific Northwest: Effect on Yields, Organic Matter. Issue 3 (15th April 2022) - Singh, Surendra; Awale, Rakesh; Machado, Stephen
Abstract : A two‐year winter wheat–fallow system in the Pacific Northwest is practiced in areas with annual precipitation <16 inches. Wheat is planted in the fall and harvested in the summer, followed by 13 to 14 months of fallow. The summer fallowing often involves different types of tillage practices to facilitate water storage and weed control, which can influence vertical distribution of soil acidity and nutrients in the profile, possibly affecting crop yields. Long‐term studies could help us understand soil nutrients and yield responses across different tillage and N rate applications. Earn 0.5 CEUs in Soil & Water Management by reading the article and taking the quiz at https://web.sciencesocieties.org/Learning‐Center/Courses .